Avoid common Clery Act compliance pitfalls, challenges. Issue 2 (June 2016) - McCarthy, Claudine
Abstract : ST. PETERSBURG BEACH, FLA. — Failure to comply with the complexities and nuances of the Clery Act comes at a high price for many colleges and universities. In fact, each criminal offense missing from campus crime reports carries a $35, 000 fine from the U.S. Department of Education. And many colleges often have 100 or more inaccuracies.